The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1074/jbc.m405345200
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of Sterols and the NPC2 Protein from Primary Astrocytes

Abstract: Astrocytes secrete cholesterol in lipoprotein particles.Here we show that primary murine embryonic astrocytes secrete endogenously synthesized cholesterol but also the cholesterol precursors desmosterol and lathosterol. In astrocyte membranes, desmosterol and cholesterol were the predominant sterols. Astrocytes derived from Niemann-Pick type C lipidosis (NPC1 ؊/؊ ) mice displayed late endosomal cholesterol deposits, but the secretion of biosynthetic sterols from the cells was not inhibited. Both wild-type and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
42
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 45 publications
5
42
0
Order By: Relevance
“…Accordingly, also in model membranes, lathosterol formed rafts that were at least as detergent-resistant as, and even more thermally stable than, cholesterol-containing rafts (13). Moreover, 7-dehydrocholesterol was found to be more strongly domain-promoting than cholesterol (17).In contrast to many relatives of cholesterol, desmosterol is an abundant structural membrane component in mammalian cells, such as spermatozoa and astrocytes (18,19). Inability to convert desmosterol to cholesterol (lack of functional 24-dehydrocholesterol reductase) leads to the human disorder desmosterolosis (20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, also in model membranes, lathosterol formed rafts that were at least as detergent-resistant as, and even more thermally stable than, cholesterol-containing rafts (13). Moreover, 7-dehydrocholesterol was found to be more strongly domain-promoting than cholesterol (17).In contrast to many relatives of cholesterol, desmosterol is an abundant structural membrane component in mammalian cells, such as spermatozoa and astrocytes (18,19). Inability to convert desmosterol to cholesterol (lack of functional 24-dehydrocholesterol reductase) leads to the human disorder desmosterolosis (20).…”
mentioning
confidence: 99%
“…In contrast to many relatives of cholesterol, desmosterol is an abundant structural membrane component in mammalian cells, such as spermatozoa and astrocytes (18,19). Inability to convert desmosterol to cholesterol (lack of functional 24-dehydrocholesterol reductase) leads to the human disorder desmosterolosis (20).…”
mentioning
confidence: 99%
“…Npc1 levels were decreased in the liver of NPC2 (h/h) mice fed a lithogenic diet. Interestingly, a reciprocal regulation in the levels of NPC1 in the NPC2 (h/h) mice was not found, whereas in various models NPC2 increases in the absence of NPC1 [13,15]. Further studies are required to elucidate the molecular mechanisms involved in this regulation.…”
Section: Discussionmentioning
confidence: 94%
“…However, it is not known whether NPC2 present in plasma is functional at neutral pH or whether it is found free or as a component of a plasma lipoprotein complex. Studies in primary astrocytes have shown that most sterols are secreted separately from NPC2 into the surrounding medium, suggesting that secreted NPC2 is not primarily associated with cholesterolcontaining particles [13]. Further studies are required to determine how NPC2 deficiency affects cholesterol levels in plasma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation